Static and dynamic responses of Halgavor Footbridge using steel and FRP materials - Gunaydin, M.; Adanur, S.; Altunisik, A. C.; Sevim, B. (TECHNO-PRESS, 2015)
In recent years, the use of fiber reinforced polymer composites has increased because of their unique features. They have been used widely in the aircraft and space industries, medical and sporting goods and automotive industries. Thanks to their beneficial and various advantages over traditional materials such as high strength, high rigidity, low weight, corrosion resistance, low maintenance cost, aesthetic appearance and easy demountable or moveable construction. In this paper, it is aimed to determine and compare the geometrically nonlinear static and dynamic analysis results of footbridges using steel and glass fiber reinforced polymer composite (GFRP) materials. For this purpose, Halgavor suspension footbridge is selected as numerical examples. The analyses are performed using three identical footbridges, first constructed from steel, second built only with GFRP material and third made of steel-GFRP material, under static and dynamic loadings using finite element method. In the finite element modeling and analyses, SAP2000 program is used. Geometric nonlinearities are taken into consideration in the analysis using P-Delta criterion. The numerical results have indicated that the responses of the three bridges are different and that the response values obtained for the GFRP composite bridge are quite less compared to the steel bridge. It is understood that GFRP material is more useful than the steel for the footbridges.
Keywords: finite element model; geometrically nonlinear static and dynamic analysis; glass fiber reinforced polymer; static analysis; suspension footbridge; CABLE-STAYED BRIDGE; COMPOSITE; PERFORMANCE; DESIGN; Construction & Building Technology; Engineering; Materials Science